AKTIVITAS EKONOMI ORANG - ORANG MINANG DI KAWASAN PASAR TANAH PILIH KOTA JAMBI 1930 - 2020 - Junaldi, Sunil; Heidi Karmela, Siti; Azmi, Ulul (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
The aim of this research to explain the reasons Minang people choose to trade at the Jambi City Market and describe the activities of Minang traders in the Jambi Market area. The method used in this research is a historical research method which consists of several stages, namely heuristics, criticism, interpretation and historiography. The main source used in this research is interviews with Minang traders at Tanah Select Market. Meanwhile, the secondary sources used are books and internet sources.The results of the research provide an explanation of the activities of Minang traders at the Tanah Select Market who have been coming to Jambi City for a long time to seek their fortune, especially at the Tanah Select Market which in the 1930s had become a very famous trading center and could generate many profits in the past. The results of this research also provide an explanation of the economic life of various Minangkabau traders at Tanah Select Market, such as Padang Sate Traders, Tailors on the Second Floor of Tanah Select Market, Gold Traders and other traders. The conclusion of this research is that the economic activities of the Minangkabau community in the Jambi City Select Land Market Area from 1930 - 2020 experienced many significant changes in several sectors, one of which is the select land tailor on the second floor which is very old but its economic activity is still running today.